Fly Guy meets Fly Girl! - Arnold, Tedd. (New York : Cartwheel Books, 2010)
When Fly Guy meets Fly Girl, he is amazed and smitten.
2.1
K-3
Keywords: Flies -- Juvenile fiction; Flies -- Fiction; Flies -- Fiction